MINERALOGY AND GEOCHEMISTRY OF MANTLE INCLUSIONS AND MANTLE COLUMN STRUCTURE OF THE YUBILEINAYA KIMBERLITE PIPE, ALAKIT FIELD, YAKUTIA - Ashchepkov I.V.; Nikolaeva I.V.; Palessky S.V.; Logvinova A.M.; Saprykin A.I.; Khmel'nikova O.S.; Anoshin G.N.; Vladykin N.V. (My University, 2004)
The mantle column structure has been defined only for the Udachnaya [1] and Mir [2] kimberlite pipes of the Siberian Platform. Peridotite xenoliths are generally serpentinized. However, their concentrate contains not only resistant minerals (garnet, ilmenite, chromite, zircon, and rutile), but also pyroxenes. This paper is based on more than 700 microprobe analyses, including more than 200 analyses of peridotite clinopyroxenes and amphiboles from the Yubileinaya Pipe (table). These data have made it possible to reconstruct the mantle column. Mantle clinopyroxenes, garnets, Cr-spinels, ilmenites, and micas from more than 20 samples were analyzed by LAM ICP-MS on a high-resolution ELEMENT Finnigan mass spectrometer